How do big data and data analytics impact the external audit ? A critical analysis - Heck, Natascha (Université de Liège, 2019)
The aim of this research is to determine how the application of Big Data and Data Analytics techniques influences the external audit. The impact on the working methods and the audit quality is discussed. Furthermore, the technological maturity of the Belgian and Luxembourgish audit industry is analysed. Therefore, the following research questions are asked: How do Big Data and Data Analytics influence the audit working method? What is the impact of Big Data and Data Analytics on the audit quality? How is the audit risk identification and assessment phase influenced? Which audit risks can be identified? Which tools and techniques do the Belgian and Luxembourgish auditors use and where do they stand? In order to answer the research question, scientific articles were analysed in the context of the literature review. Subsequently, a case study was carried out. Interviews with experts in Belgium and Luxembourg were conducted. The results of the research show that there is high potential to use these technologies in audit. Nevertheless, it is also connected with initial investments and a certain agreement of the clients. There is high potential to enhance the auditor’s effectiveness and efficiency, but the complete impact cannot yet be analysed. The audit quality can be enhanced when qualitative analyses generates audit evidence based on high quality data. The Belgian and Luxembourgish audit industry has just started implementing the technologies.
Keywords: Audit; Big Data; Data Analytics; External Audit